DAMPAK KETERGANTUNGAN PENGGUNAAN ARTIFICIAL INTELLIGENCE (AI) TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA MAHASISWA DI INDONESIA - Rafi Swarna Erlangga Putra; Niken Widi Astuti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The rapid development of Artificial Intelligence (AI) has facilitated students in completing academic tasks; however, it has also increased the risk of dependency that may affect their critical thinking skills. This study aims to examine the influence of AI dependency on critical thinking skills among university students in Indonesia. A quantitative research approach was employed, involving 408 students aged 18–23 years selected using purposive sampling. AI dependency was measured using the Dependence on Artificial Intelligence (DAI) Scale, while critical thinking skills were assessed using the Critical Thinking Questionnaire (CThQ). The Spearman correlation test indicated a strong and significant positive relationship between AI dependency and critical thinking skills (r = 0.759, p = 0.000). Furthermore, a simple linear regression analysis revealed that the regression model was significant (F = 585.152, p = 0.000), and that AI dependency contributed 59% (R² = 0.590) to the variance in critical thinking skills. The regression coefficient also demonstrated a significant positive effect (B = 0.371; β = 0.768; t = 24.190; p = 0.000). These findings suggest that the higher the students’ dependency on AI, the higher their critical thinking skills. Therefore, digital literacy and proper education regarding the use of AI are needed to ensure that the technology supports the development of students’ cognitive quality.